Influence of school plant variables on the performance of technical education students in Nigeria University (A case study of ambrose Alli University) - Osamede, Ogbebor Samuel (INVOTEC, 2023)
This study observed the effects of school plant variables on the performance of technical education students. The correlational survey research design was adopted for the study. The study sampled is Ambrose Alli University ( AAU), Ekpoma,. 50 technical education students in the department of vocational and technical education were used,  no sampling method was used as all the technical education students were used for the study. A researcher- designed  questionnaire titled ‘School Plant Variables  Questionnaire” (SPVQ) was used to collect data on relative organization and utilization of school plant facilities in the schools. The construct and content validity of the instrument was done by experts in research. The questions items were reviewed by the specialists and corrections were affected as suggested by them. After a test- retest treatment within two weeks interval, the scale recorded a cronbach alpha of 0.75. The study found out that  school plant facilities (Classrooms,  workshops, relaxation centres) were located considerable distance from where students resides thus requiring longer time for  students to move into or from them for teaching and learning. Also, a significant relationship was established between school plant organization and utilization on academic performance with F- value (0.36) critical F- value (0.19) at 05 level of significance. School plant organization and utilization on student attendance/ punctuality at lessons were found to be significantly related with F-value (0.7921) critical F- value (0.16) at .05 level of significance. The study concluded that school plant organization and utilization have a role to play on the effectiveness of instruction and the ultimate performance of students in their examinations. It thus recommended the construction of ‘Integrated Classrooms’ that can house almost all teaching and learning activities, with relaxation centres under one big roof and hostel accommodation to accommodates all students closer to the big roof building.